Dosimetric Predictors of Acute and Chronic Alopecia in Primary Brain Cancer Patients Treated With Volumetric Modulated Arc Therapy - Scoccianti, Silvia; Simontacchi, Gabriele; Greto, Daniela; Perna, Marco; Terziani, Francesca; Talamonti, Cinzia; Teriaca, Maria Ausilia; Caramia, Giorgio; Lo Russo, Monica; Olmetto, Emanuela; Delli Paoli, Camilla; Grassi, Roberta; et al. (Frontiers in Oncology, 2020)
Purpose: To determine dose constraints that correlate with alopecia in patients treated with photon-based Volumetric Modulated Arc Therapy (VMAT) for primary brain tumors. Methods: During the treatment planning process, the scalp was drawn as a region of interest. Dose received by 0.1 cc (D0.1cc), mean dose (Dmean), absolute volumes receiving different doses (V16Gy, V20Gy, V25Gy, V30Gy, V35Gy, V40Gy, and V43Gy) were registered for the scalp. Alopecia was assessed according to Common Terminology Criteria for Adverse Events (CTCAE) v4.0. Receiver operating characteristics (ROC) curve analysis was used to identify parameters associated with hair-loss. Results: One-hundred and one patients were included in this observational study. At the end of radiotherapy (RT), 5 patients did not develop alopecia (Dmean scalp 3.1 Gy). The scalp of the patients with G1 (n = 11) and G2 (n = 85) alopecia received Dmean of 10.6 Gy and 11.8 Gy, respectively. At ROC analysis, V16Gy20Gy ≥ 5.2 cc were the strongest predictors of acute alopecia risk. Chronic hair-loss assessment was available for 74 patients: median time to recovery from G2 alopecia was 5, 9 months. The actuarial rate of hair regrowth was 98.1% at 18 months after the end of RT. At ROC analysis, V40Gy43Gy ≥2.2 cc were the strongest predictors of chronic G2-alopecia risk. V20Gy, V40Gy, and D0,1cc were shown to be independent variables according to correlation coefficient r. Conclusions: V20Gy and V40Gy were the strongest predictors for acute and chronic G2 hair-loss, respectively. The low-dose bath typical of VMAT corresponds to large areas of acute but transient alopecia. However, the steep dose gradient of VMAT allows to reduce the areas of the scalp that receive higher doses, minimizing the risk of permanent alopecia. The application of our dosimetric findings for the scalp may help in reducing the alopecia risk and also in estimating the probability of hair-loss during patient counseling before starting radiotherapy.